In Vitro and In Vivo Effects of Human Monocytes and their Subsets on New Vessel Formation. (February 2014) - Czepluch, Frauke S.; Bernhardt, Markus; Kuschicke, Hendrik; Gogiraju, Rajinikanth; Schroeter, Marco R.; Riggert, Joachim; Hasenfuss, Gerd; Schäfer, Katrin
Abstract Objective Human monocytes can be divided into CD16− monocytes and CD16+ monocytes. Studies in mice suggested differential effects of monocyte subsets during new vessel formation. Methods The functional role of human monocyte subsets in neovascularization processes was investigated. For in vivo experiments, nude mice underwent unilateral hindlimb ischemia surgery before being injected with either total monocytes, CD16− monocytes or CD16+ monocytes isolated from healthy individuals. Results In vitro, cytokine array analysis demonstrated that monocytes release numerous angiogenic cytokines, some of which were differentially expressed in monocyte subsets. Sprout length was enhanced in EC spheroids being cultured in conditioned medium obtained from total monocytes and, to a lesser extent, also in supernatants of CD16− monocytes. Laser Doppler perfusion imaging up to day 28 after surgery revealed a trend toward improved revascularization in mice treated with monocytes, but no significant differences between monocyte subsets. Histological analyses four weeks after surgery showed an increased arteriole size in mice having received CD16+ monocytes, whereas the number of capillaries did not significantly differ between groups. Conclusions Our findings suggest additive and differential effects of monocyte subsets during neovascularization processes, possibly due to an altered secretion of angiogenic factors and their paracrine capacity to stimulate new vessel formation.